Projeções urbanas: um estudo sobre as formas de representação e mobilização do tempo na construção de Belo Horizonte, Goiânia e Brasília - Cristiano Pereira Alencar Arrais (2008)
This work encompasses the issue on the ways of representation and mobilization of experience one has with time. To do so, I have taken the process of planning and building of three capital-cities in Brazil as the locus of study: Belo Horizonte (1987), capital of Minas Gerais State; Goiânia (1942), capital of Goiás State; and Brasília, capital of Brazil, inaugurated in 1960. The evaluation and reconstruction of the concepts of time - a social product that is able to indicate the way individuals comprehend and create their relationship with the world -, and narrative - as an ontological-explanatory necessity and mechanism of orientation aiming the constitution or strengthening of consensus - have worked as heuristic tools for an approximation of expectation horizons implicit in the documentation utilized: historical works - here understood as ways of reconstructing the past, made concrete linguistically - produced in the period of construction of the three new capitals (Traços históricos e descriptivos de Bello Horizonte, from 1897, Como nasceu Goiânia, from 1938, and Coleção Brasília, from 1960) and the technicalurban documentation originated from their respective planning and construction processes. In the first part I stress the rhetoric procedures and the reconstructive basis which each of those historical works makes use of: such as memory, documental truth, and intellectual reconstruction. In the second part I try to identify the modes of narrative composition that are implicit in the technical-urbanistic thought implied in the planning and construction of each of the new capitals and in the ways such modes were utilized to represent their own time and mobilize ideas, emotions and the individuals. These expectations, projected and fixed in this documentation, were able to crystallize a certain way for their own time and influence how it was understood and experimented